APAKAH LITERASI KEUANGAN MAMPU MEMPERLEMAH PERILAKU KONSUMTIF MAHASISWA? - Anna Kania Widiatami; Afrida unti Fatimatuzzahro; Dwi Puji Astuti; Saringatun Mudrikah (Value : Jurnal Manajemen dan Akuntansi, 2023)
Excessive consumptive behavior has a negative impact on students, such as a hedonic lifestyle, an uncontrollable shopping appetite and a tendency to have no savings in the future. The purpose of this study was to analyze the effect of using e-wallets, lifestyle, and family economic conditions on consumptive behavior with financial literacy as a moderating variable. The research population was 115 students of the Faculty of Economics and Business UNNES Bachelor of Economics and Accounting Education class of 2019. The sample was calculated using the Slovin formula so that a total of 89 students were obtained. The sampling technique used is simple random sampling or random sampling. Research data was collected using a questionnaire with the help of google form. The data analysis technique used is descriptive analysis and PLS Structural Equation Modeling (SEM) analysis. The conclusion of this study is that the use of e-wallets and lifestyle have a positive and significant effect on consumptive behavior. The family's economic situation has no effect on consumptive behavior and financial literacy cannot weaken the relationship between e-wallet use, lifestyle and family economic conditions on consumptive behavior. Keywords: E-Wallet, Lifestyle, Family Economic Situation